URUTAN PARSIAL PADA SEMIGRUP DAN PADA KELAS-KELAS DARI SUATU SEMIGRUP - Irtrianta Pasangka Irtrianta Pasangka (MATEMATIKA FSM, UNDIP, 2016)
ABSTRACK. Non empty set with binary operation is called semigroup if the binary operation on is associative. An element a of semigroup is called regular if there exist such that and semigroup is called invers if there exist such that dan . Partial order is relation which is satisfy reflexive, antysymetric and transitive. Relation dan is equivalent relation. Let be semigroup and relation for every , is class that contain . Thus obtain on relations dan . Relation is called partially order relation of regular semigroup if for any , if and only if and for some . Relation is called partially order relation of regular semigroup if for any , if and only if for some .